Role of Mathematical Self-Efficacy and Self-Concept in Mathematics Achievement: A Structural-Motivational Model - Güzeller, Cem Oktay; Akin, Ayça (Mediterranean Journal of Humanities, 2017)
Mathematical self-efficacy and mathematical self-concept are motivational elements of social- cognitive theory. This theory proposes that mathematical self-efficacy and mathematical self-concept are better mediators or predictors of mathematics achievement than affective-motivational and background variables. Therefore, the aim of the research is to investigate a structural-motivational model of mathematics achievement for a low performing country in the PISA (Turkey) based on the integration of Ferla, Valcke and Cai’s (2009) model of mathematical self-efficacy and self-concept for a high performing country in the PISA (Belgium). Important finds from the model indicates: (a) mathematical self-efficacy was more predictive of mathematics achievement than is mathematical self-concept, mathematics anxiety, mathematics interest, grade level, or gender, while mathematical self-concept is a better mediator for affective-motivational variables on mathematics achievement than the other variables; (b) students’ mathematical self-efficacy strongly influenced their mathematical self-concept and not vice versa; (c) surprisingly, mathematics interest has a negative influence on mathematics achievement; and (d) the proposed model explained 34% of the variance in mathematics achievement. These results show the importance of academic motivation in the prediction of mathematics achievement for low performing and high performing countries in the PISA.
Keywords: Educational Sociology; Mathematical Self-Efficacy; Mathematical Self-Concept; Mathematics Anxiety; PISA; Eğitim Sosyolojisi; 4. Education; 10. No inequality